2011
DOI: 10.1093/annonc/mdq720
|View full text |Cite
|
Sign up to set email alerts
|

Incidental versus symptomatic venous thrombosis in cancer: a prospective observational study of 340 consecutive patients

Abstract: A high proportion of venous thrombotic events in cancer patients are diagnosed incidentally during scheduled imaging. Prospective controlled trials evaluating the optimal therapy in this setting are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 22 publications
7
49
1
1
Order By: Relevance
“…Likewise, in a prospective observational study, Font et al. [6] reported a similar overall survival between cancer patients with a symptomatic VTE and cancer patients with an incidental VTE. Finally, in a matched cohort study of cancer patients diagnosed with an incidental PE on routine staging scans, O’Connell et al.…”
Section: Baseline Characteristics Of the Study Populationmentioning
confidence: 82%
“…Likewise, in a prospective observational study, Font et al. [6] reported a similar overall survival between cancer patients with a symptomatic VTE and cancer patients with an incidental VTE. Finally, in a matched cohort study of cancer patients diagnosed with an incidental PE on routine staging scans, O’Connell et al.…”
Section: Baseline Characteristics Of the Study Populationmentioning
confidence: 82%
“…Of these 94 patients, 26 were lung cancer patients. Investigators concluded that IVT is common, especially in patients with advanced age, metastatic disease, and usually involves larger vessels [81]. Despite the frequency of IVT, the impact it has on the patient is not fully understood, and no consensus on treatment has been reached due to the lack of proper studies in this field [82].…”
Section: Diagnosismentioning
confidence: 99%
“…As suggested by others, incidental VTE may thus be a marker of poor prognosis, independent of other confounders such as age, malignancy and adequacy of anticoagulation [8]. Although controversial [6], incidental VTE in patients with cancer may also reflect a more aggressive course of cancer as suggested previously [10].…”
mentioning
confidence: 75%